ECONOMETRIC MODELS OF INCREASING THE EFFICIENCY OF PROCESSES USING ALTERNATIVE ENERGY SOURCES - Qodirov Baxodir Tursunovich (Scholar Express Journals, 2022)
In this article, the qualitative and quantitative indicators affecting the effectiveness of the use of alternative energy sources are studied, the criteria determining the economic potential are analyzed and their composition is compiled. Also, the processes of using alternative energy sources and the factors affecting it were analyzed and their quantitative effects were evaluated based on econometric models
Keywords: renewable energy; alternative energy sources; econometric models; evaluation indicators